2018
DOI: 10.1002/cssc.201800878
|View full text |Cite
|
Sign up to set email alerts
|

Water Splitting–Biosynthetic Hybrid System for CO2 Conversion using Nickel Nanoparticles Embedded in N‐Doped Carbon Nanotubes

Abstract: CO reduction has drawn increasing attention owing to the concern of global warming. Water splitting-biosynthetic hybrid systems are novel and efficient approaches for CO conversion. Intimate coupling of electrocatalysts and biosynthesis requires the catalysts possess both high catalytic performance and excellent biocompatibility, which is a bottleneck of developing such catalysts. Here, a complex of Ni nanoparticles embedded in N-doped carbon nanotubes (Ni@N-C) is synthesized as a hydrogen evolution reaction e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 55 publications
(122 reference statements)
2
19
0
2
Order By: Relevance
“…For the other Ni based catalysts, the XPS spectra of the Ni 2p (Figure S18a) all exhibit two main peaks at 853.3 ± 0.3 eV and 870.5 ± 0.3 eV without any obvious satellites, corresponding to the metallic dominant structure. Two weak peaks are assigned to NiN x (855.3 ± 0.3 eV) and NiO (856.8 ± 0.3 eV, oxidized in the air),respectively [77][78][79][80]. The similar results for Co based catalysts with different locations of peaks (for Co 0 , CoN x and CoO)16,[81][82][83] are shown in (Figure S18b), which indicates Co 0 as the dominant chemical states of Co.…”
supporting
confidence: 52%
“…For the other Ni based catalysts, the XPS spectra of the Ni 2p (Figure S18a) all exhibit two main peaks at 853.3 ± 0.3 eV and 870.5 ± 0.3 eV without any obvious satellites, corresponding to the metallic dominant structure. Two weak peaks are assigned to NiN x (855.3 ± 0.3 eV) and NiO (856.8 ± 0.3 eV, oxidized in the air),respectively [77][78][79][80]. The similar results for Co based catalysts with different locations of peaks (for Co 0 , CoN x and CoO)16,[81][82][83] are shown in (Figure S18b), which indicates Co 0 as the dominant chemical states of Co.…”
supporting
confidence: 52%
“…The electrochemical CO 2 reduction reaction (CO 2 RR) has been recognized as a promising strategy to convert problematic CO 2 into value-added feedstocks, thanks to the multiple advantages of the electrochemical route, including mild conditions (i.e., ambient pressure and room temperature), potential synergy with renewable energy, and product tunability. [1][2][3][4][5][6][7] However, the electrochemical CO 2 RR occurs at a potential close to that of the hydrogen evolution reaction (HER), inevitably leading to a rather low selectivity toward the CO 2 RR since the HER is thermodynamically more favorable in most electrocatalysts. Moreover, the development of advanced CO 2 RR electrocatalysts still faces issues of high overpotential, low efficiency, slow kinetics, and poor stability.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new electrode materials provides another way of mitigating ROS toxicity. Wang and colleagues developed a polyoxometalate (POM) water splitting system that showed negligible production of hydrogen peroxide during water splitting, [30] while separate work showed that embedding nickel nanoparticles in n‐doped carbon nanotubes minimized Ni 2+ leaching and ROS generation [31] . A ROS‐resistant cobalt phosphorous (Co−P) alloy cathode combined with a self‐healing CoPi anode that scavenges leached cobalt ions simultaneously provides a solution to the problems of ROS generation and electrode leaching [32] .…”
Section: Combining Electrochemical Systems With Living Cellsmentioning
confidence: 99%